Food chemicals codex : by authority of the United States Pharmacopeial Convention (United States Pharmacopeial Convention, 2010)
The Food Chemicals Codex (FCC), Tenth Edition, will feature more than 1,200 monographs, step-by-step methods, and helpful information for manufacturers, suppliers, and users of food ingredients. This edition will include an excerpt from USP's Food Fraud Database, comprising more than 2,000 entries of adulterants reported for specific ingredients from 1980-2012.